Inventario de los principales movimientos de masa presentes en el barrio San Cayetano de la Ciudad de Loja y su área de influencia directa. - Japón Capa, Dolores Eufemia (2010)
The Sector of San Cayetano specifically the Neighborhood of San Cayetano is a populated area of the city of Loja that is affected by different mass movements due to the climatic conditions and litológicas belonging to the Formation San Cayetano whose characteristics are of litologías clays, gritty, shales, diatomitas that favor to the occurrence of slips. The growth urbanístico of the city of Loja is evident, of there the necessity of a classification territorial chord to the conditions of the land in order to avoid economic losses and the most important thing to avoid loss of human lives, this sector has been chosen due to the serious problems by slips that one has come evidenced through the times. The development of maps of susceptibility determines stable areas or areas of high susceptibility to movements this way one can make an orderly planning of the sector. The inventory of mass movements makes a detailed description of the movement type, characteristic, location of each movement that also united to the process antrópico they alter the stability of the land, this way the first step is taken in the identification of mass movements and the possible solutions, with the purpose of acting on time before these events of those that we expose ourselves to newspaper.